PENGARUH METODE ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK DI SEKOLAH DASAR - Susanti, Ayu; Marzuki, Marzuki; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract         This study aims to analyze the influence of role playing methods on the speaking skills of class V students of State Elementary School 36 Pontianak Selatan. The research method used is experimental method, while the research form used is one group pre-test and post-test. In this study, the samples are students of VA class as many as 22 students. Data collection techniques used in this study is a measurement technique with the scoring of speaking skills of learners. Based on result of data analysis from mean value of result of pre-test 43,633 and post-test average 73,029. T test result obtained ttable at significant level ? = 5% is 2,080. Because thitung (8,466)> ttable (2.080) then hypothesis testing of post-test data is accepted. From the calculation of effect size (ES), obtained by 0.1107 with the role playing method gives a low influence to the speaking skills of students in grade V of State Elementary School 36 Pontianak Selatan.          Keywords: Influence, Role Playing Method, Speech Skill, Bahasa Indonesia.